Comparison of Rapidec Carba NP test versus modified Hodge test in Finding Frequency and Resistance Pattern of E. Coli and Klebsiella Species - Faisal, Hina; Idris, Azra; Siddiqui, Hira Zafar; Razak, Sadaf; Yaseen, Maliha; Faisal, Amber (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To compare the investigations that would ultimately benefit the healthcare professionals to opt for better management against the disease process on time. METHODOLOGY: This cross-sectional study was conducted at Lifeline General Hospital, Karachi, from March to November 2023. The CLSI guidelines for isolates showing inhibition zone size of antimicrobial agents were documented as potential carbapenemase producers and short-listed for confirmation of carbapenemases and their respective classes. SPSS 22 was used to analyze data. A chi-square test was used, keeping a p-value of < 0.05 as significant. RESULTS: The frequency of positive and negative samples was recorded as 287 (75.5%) and 93 (24.4%), respectively. The distribution of microorganisms within samples indicated the presence of E. coli at 47 (12.3%), 18 (4.7%), 21 (5.5%), and 4 (1%) in urine, pus, respiratory tract, and blood samples, respectively. The distribution and identification of microorganisms, as reported using the techniques employed, yielded no statistically significant results, with p-values of 0.81 and 0.26 for E. coli and Klebsiella, respectively. CONCLUSION: This study concludes that Carba NP is a cost-effective option, providing rapid results within 30 to 120 minutes. The high specificity and sensitivity of the test contribute to improved patient management and the prevention of healthcare-associated infections.